Satellite Image Classification by Fuzzy Neural Network - Abood, Loay; Ibrahim, Fatima (Iraqi Journal of Science, 2025)
Implementation of Fuzzy Reasoning by stimeture of Neural Network method is used in this work, weights of Neural Network is Fuzzy Reasoning. The FNN can automatically identity the Fuzzy Rules and tune the membership function by modliying the connection weights of Network using the back-propagation algorithun, Post-classification marles is used to redarce the number of isolated mis-classified pixels occur after the pixel-by-pixel classification principle.